Horti-Cultural Space: To Learn, Heal, and Grow - Dini Farhana Baharudin; Ainurliza Mat Rahim; Nurhafizah Mohd. Sukor (Penerbit USIM, 2025)
International Language and Education Innovation Competition 2024 (I-INNOLED 2024) E-Proceedings International Language and Education Innovation Competition 2024 (I-INNOLED 2024) “Navigating The Future of Language And Education In A Transformative Era” 15-16 October 2024 Organized by : Faculty Of Major Language Studies Editors: Lubna Abd. Rahman, Amiliayanti Abd Halim, Maziahtusima Ishak